IDENTIFICATION OF THE SUBSURFACE STRUCTURE USING GRAVITY METHOD IN THE SUMBERMANJING WETAN AND DRUJU VILLAGE - SOUTH MALANG - Ramadhani, Winda; S.Si, M.Si, DR Sunaryo; M.AB, Drs. Wasis (Department of Physics - Faculty of Science, 2014)
Geophysical studies have been carried out by the method of gravity in the Sumbermanjing Wetan and Druju Village using gravitimeter La Coste & Romberg G-type 1053 with a 250-meter intervals spread over an area of ââ4x4 kmÂ² with 117 of measuring points. Data processing is performed to obtain a complete Bouguer anomaly. A Complete Bouguer anomaly is projected onto a flat surface by the method of Dampney and carried outÂ by separation ofÂ local and regional anomalies. Separation of local and regional anomalies carried by upward continuation method at an altitude of 1300 m from the flat surface. Interpretation of local anomalies are qualitatively show anomalous low value, meanwhile anomalous high value is interpreted by the presence of sedimentary rocks. Quantitative interpretation of the 2D polygon method shows the subsurface structure of area observation which produces four types of rock consisting of clay rock, sandy marl, sandstone and limestone. Â Keywords: gravity, subsurface structure, Bouguer Anomaly